The wealthy Portuguese culture of giving - Andrade, Inês Freire de (2018)
This thesis studies the Portuguese wealthy donors, in what concerns the motivations that drive their donations, the path they pursue to go from non-donors to loyal supporters, as well as the potential blockages in that path. To support this work, an international literature review was made, adding to six semi-structured interviews to representative individuals, to provide with insights from real Portuguese wealthy donors. Some recommendations were made to the nonprofit institutions, in order to engage better with donors and promote more donations.